An Orientalist Discovery Effort During the 19th Century through the Eyes of Some European Travelers in Ankara - Muhsin Önal (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Ankara, located in the center of Asia Minor and founded on an important crossroads, has always been an attraction center for travelers of various religious and national backgrounds. More importantly, it was located on the King’s Road which extended from Mesopotamia to Western Anatolia. Undoubtedly, these characteristic features of the city were noticed by Western travelers. The city was first visited by a Western traveler in the 16th century. The number and frequency of these trips increased over time. The 19th century is considered as the peak point in this regard. Correspondingly this article focused on the opinions of five different Western travelers who visited Ankara during the 19th century and whose names came into prominence. Before that, the period from the 16th to the 19th century was examined. In some cases, Ottoman archival documents were used to check the data provided by the travelers’ resources.